2004
DOI: 10.1111/j.1523-1755.2004.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

Losartan modulation on NOS isoforms and COX-2 expression in early renal fibrogenesis in unilateral obstruction

Abstract: These results allowed us to infer an interstitial fibrogenesis prevention independent action of losartan, involving NOS isoforms and COX-2, in unilateral obstructive nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 53 publications
2
34
1
3
Order By: Relevance
“…2) Losartan treatment reduced the increased COX-2 protein and mRNA expressions and the increased release of PGF 2␣ and 8-isoprostane found in aortic segments from SHR, without further effects by the COX-2 inhibitor NS-398 in this release. In this line of evidence, losartan treatment is reported to decrease the increased inducible nitric-oxide synthase and COX-2 expression observed after experimental renal interstitial fibrosis (Manucha et al, 2004). However, the AT 1 receptor blocker candesartan has also been reported to increase the renocortical COX-2 mRNA expression in 5-week-old SHR, but it has no effect in older rats (Hocherl et al, 2001).…”
Section: At 1 Receptors and Cox-2 In Hypertension 385mentioning
confidence: 83%
“…2) Losartan treatment reduced the increased COX-2 protein and mRNA expressions and the increased release of PGF 2␣ and 8-isoprostane found in aortic segments from SHR, without further effects by the COX-2 inhibitor NS-398 in this release. In this line of evidence, losartan treatment is reported to decrease the increased inducible nitric-oxide synthase and COX-2 expression observed after experimental renal interstitial fibrosis (Manucha et al, 2004). However, the AT 1 receptor blocker candesartan has also been reported to increase the renocortical COX-2 mRNA expression in 5-week-old SHR, but it has no effect in older rats (Hocherl et al, 2001).…”
Section: At 1 Receptors and Cox-2 In Hypertension 385mentioning
confidence: 83%
“…Following 24-h complete UUO in the adult rat, renal cortical COX-2 decreases, while medullary COX-2 increases (10). In this regard, COX-2 inhibition attenuates progressive renal injury in the adult rat subjected to complete UUO (33), and losartan decreases renal COX-2 expression and reduces fibrosis resulting from UUO (30). Similarly, candesartan reduces renal medullary COX-2 induction and ameliorates renal function following release of bilateral ureteral obstruction in the adult rat (23).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, a non-hemodynamic effect of angiotensin II as a profibrotic cytokine, contributing to renal injury, can be included in LP as demonstrated in other experimental models (Klahr et al 1988;Ishidoya et al 1995;Manucha et al 2004). Besides its effect on cell proliferation and growth, angiotensin II has been shown to induce apoptosis (Ding et al 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Evidence involving angiotensin II in altered renal non-hemodynamics, leading to the tubulointerstitial injury, has been reported. For these events, angiotensin II promotes the synthesis of several cytokines and growth factors that contribute to the progression of the renal injury (Kaneto et al 1994;Manucha et al 2004). Moreover, studies have recently shown that angiotensin II can stimulate oxidative stress (Pueyo et al 1998).…”
Section: Introductionmentioning
confidence: 99%